” PERFORMANCE ANALYSIS OF THE ROAD ON THE ROAD SECTION SOEKARNO - HATTA KM . 37 + 00 TO KM . 57 + 00 - ABDUL WAHAB (KURVA MAHASISWA, 2015)
Abdul Wahab , NPM : 10.11.1001.7311. 225 , Street Performance Analysis On The Road Soekarno - Hatta Segment KM . 37 + 00 TO KM . 57 + 00 , Supervisor I : Ir. Yayuk Sri Sundari, MT And Supervisor II : Rosa Agustaniah, ST.,MTIt is the capital city of Samarinda in East Kalimantan has a mining license The Very strategic That connects several districts / cities in the area are the initials , so that the growth of the city of Samarinda High Enough EVERY year. BETWEEN initial situation causes an imbalance in the Period Vehicle WITH capacity Yang Number : Available , so the issue of Traffic and Traffic Accidents And Vehicles queue length .As Happens at Soekarno Hatta Street Segment - KM . 37 + 00 TO KM . 57 + 00 in the area are the initials Many vehicles passing by . FOR THAT THERE Must Re- evaluation of the boarding costs went down the road .Composition Composition Of Husband research is to analyze the boarding costs pada road street sunset Soekarno - Hatta KM 37 + 00 Up to KM 57 + 00Composition Composition Of Research husband is Astra Honda Motor as follows : 1. Analyze the Initial ConditionsAnalyze the condition changes during peak hours Passes Traffic And the average - average boarding costs went down the road at rush hourFrom the analysis of Jalan Soekarno - Hatta KM 37 + 000 – KM 57 + 000 To conclude ;a. Vehicle flow ( Q )- Segment I: 579 km / hour- Segment II : 497 km / hourb . Capacity ( C )- Segment I: 561 smp / hour- Segment II : 476 smp / hourc . The degree of saturation ( DS ) - Segment I: 0.22 - Segment II : 0.19d . barriers side - Segment I: 84 Indicators of Genesis ( L ) Low - Segment II : 83 Indicators of Genesis ( L ) Lowe . SPEED And Travel Time - Segment I: 59.07 km / h and takes 6.1 seconds - Segment II : 57.63 km / h and takes 6.1 seconds 2. Based Indicators index Service Level ( Level of Service ) / LOS Roads Soekarno Hatta ( Samarinda - Balikpapan ) Kilometer 37 s/d 57 Kilometers is :The ratio obtained L.o.S = V / C - Segment I: 579 / 2593.5 = 0.22 < 0.85 = A - Segment II : 497 / 2593.5 = 0.19 < 0.85 = A Indicators derived from the index calculation Service Level A OR < 0.85 it can be concluded that free prepaid Flow , Low Volume , High SPEED , and Drivers MAY require speed , expandabilas SPEED What is desired .